The Hedonics of Debt - Shin, Faith; Cohen, Dov; Lawless, Robert M.; Preston, Jesse L. (Frontiers in Psychology, 2020)
Psychologists and economists often discuss the “pain” of paying for our purchases. Four experiments examine how people evaluate prospective debt payments, analyzing how different features of a loan (down payment, final payment, duration, monthly payments) affect willingness to accept the loan. Akin to previous findings on physical pain, participants exhibited duration neglect and over-weighted final moments. However, participants also focused heavily on the monthly or average payment (unlike in retrospective studies of physical pain where only peak-end moments seem to count). In Experiment 2, participants’ willingness to accept the loan was not significantly diminished by making it more expensive through keeping the same monthly payment but extending the length of the loan by 40 percent (evincing duration neglect). Further, in Experiments 3 and 4, we show that participants increased their willingness to buy if loans were made longer and more expensive by adding smaller, less “painful” payments to the end.